The significance of religion on positive and negative body image in adolescents: A psychology of religion review - Lumban Gaol, Gabriela; Ranimpi, Yulius Yusak; Prayitno, Iky Sumarthina Putri (Institut Agama Islam Negeri Langsa, 2024)
Biological, cognitive, and socioemotional changes occur in adolescents. Teenagers pay more attention to physical appearance and body shape based solely on personal judgment or society's views, without looking at other aspects, such as religion. Therefore, the purpose of this study was to describe and analyze the significance of religion in teenagers' body image from the perspective of the psychology of religion. The method used was qualitative with a phenomenological study design. Data collection techniques included observation, interviews, and documentation. The research participants totaled four people, three of whom had a positive body image and one other had a negative one. The results showed that religion was related to body image. Participants with a positive body image consider that they have been created by God perfectly, and they are grateful for everything about themselves and their appearance. Participants with a negative body image recognized that God had indeed created all humans good, but participants always felt dissatisfied with themselves, so participants continued to think about and improve things that they felt were not good. Most importantly, all participants acknowledged that religion guided them in finding meaning and purpose in life. Religion provides a strong basis for building a positive and healthy body image by thinking, responding to every event, and reflecting on or self-evaluating. This study implies that each individual is aware of the importance of self-acceptance, seeing, and thinking that the self is valuable and special.